2019
DOI: 10.1002/ijc.32291
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian analysis of baseline risk of CIN2 and ≥CIN3 by HPV genotype in a European referral cohort

Abstract: Whereas HPV16 and HPV18 have been the focus in current risk‐based cervical cancer screening algorithms using HPV genotype information, mounting evidence suggests that oncogenic HPV types such as HPV31, 33, 52 and 58 pose a ≥CIN3 risk equivalent to or greater than that of HPV18, and the combined risk of HPV31 and HPV33 rivals even HPV16 in women above 30 years of age. Here, we evaluate the baseline risk of CIN2 and CIN3 by genotype in a colposcopy referral population from Denmark and Italy. In total, 655 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 51 publications
(113 reference statements)
1
29
0
Order By: Relevance
“…The clinical importance of these observations is the demonstration of the ability of the Onclarity assay to precisely detect clinically relevant HPV infections at the individual genotype level. This information can be used with advanced screening algorithms where individual follow-up recommendations are issued for women with HPV16 and -18 found in screening samples or, as recently proposed by us (26) and shortly to be adopted in the Danish screening program, where individual screening recommendations are issued for samples positive for HPV16, -18, -31, -33, and -51, which pose an overall higher risk of ՆCIN2 than the remaining hrHPV genotypes (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical importance of these observations is the demonstration of the ability of the Onclarity assay to precisely detect clinically relevant HPV infections at the individual genotype level. This information can be used with advanced screening algorithms where individual follow-up recommendations are issued for women with HPV16 and -18 found in screening samples or, as recently proposed by us (26) and shortly to be adopted in the Danish screening program, where individual screening recommendations are issued for samples positive for HPV16, -18, -31, -33, and -51, which pose an overall higher risk of ՆCIN2 than the remaining hrHPV genotypes (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown -by Bayesian probability modeling -that there is the highest risk of HSIL+ in HPV16-positive patients; furthermore, HPV31-and HPV33/58-positive patients have a higher risk of HSIL+ compared to HPV18-positive patients [28]. A European study showed that the most common HPV types in women with HSIL and cervical cancer were HPV16/33/31 (59.9/10.5/9.0%) and HPV16/18/45 (63.3/15.2/5.3%), respectively [29].…”
Section: Discussionmentioning
confidence: 99%
“…HPV16 confers the largest risk in women below 30 years of age (26), whereas HPV16 in combination with 18, 31 and 33 together constitute the highest relative risk of disease in women above 30 years of age (26)(27)(28)(29). Data on the absolute risk of CIN by individual HPV genotypes and the fast evolution of cervical screening technology makes it increasingly relevant to consider HPV type specific risk-based screening algorithms (19,30). From a guideline perspective, risk stratification based on HPV16 and HPV18 is already incorporated into a number of national guidelines for triage of HPV positive screening samples (31), as standalone referral indication for colposcopy or as part of a combined outcome with cytology findings of atypical squamous cells of undetermined significance (ASCUS) or low-grade squamous intraepithelial lesion (LSIL) in certain settings (28,30,32,33 Here, we assessed the clinical performance of the CLART4S assay relative to that of the comparator assay MGP-PCR (Modified General Primers GP5+/6+ with genotyping using Luminex (BioRad) assay) using the international guidelines for primary cervical cancer screening (4).…”
Section: Introductionmentioning
confidence: 99%